2003
DOI: 10.1046/j.1525-1497.2003.20351.x
|View full text |Cite|
|
Sign up to set email alerts
|

Promoting signing of advance directives in faith communities

Abstract: OBJECTIVE:To develop a participatory educational program implemented in faith communities that would increase discussion and signing of two types of advance directives-living will and durable power of attorney for health care decisions. DESIGN: MAIN RESULTS:Two hundred forty-eight (69%) of the congregants who started the program completed it. Of the program completers, 83 (33%) had a directive prior to the program and 140 (56%) had a directive after completion. One hundred eighty-six of the completers discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 23 publications
0
12
1
Order By: Relevance
“…Medvene et al achieved an increase in AD completion of 23% in 17 of their faith communities [31]. While studies among African Americans [32, 44] found that spiritual beliefs facilitated end-of-life decision-making, in our study, spiritual beliefs were not significantly associated with either AD completions or proxy conversations.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Medvene et al achieved an increase in AD completion of 23% in 17 of their faith communities [31]. While studies among African Americans [32, 44] found that spiritual beliefs facilitated end-of-life decision-making, in our study, spiritual beliefs were not significantly associated with either AD completions or proxy conversations.…”
Section: Discussioncontrasting
confidence: 70%
“…In previous studies, perceived higher social support from their religious community was associated with higher odds of AD completion [31, 32, 44]. Other studies suggest that older church attendees look to their churches for social and spiritual support and guidance on end-of-life issues [21, 45, 46].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A similar pattern was found in one study of buffering against fear of death, which may be associated with having a DNR order (29). Some educational groups have reached out to religious congregations in an effort to encourage end-of-life planning (30-32), perhaps influencing the most religious or spiritual patients. Alternatively, the religious patients in our sample may have been part of religious communities that encourage such planning.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-six percent of the 248 participants that completed the program either revised an existing AD or completed one for the first time. Thirty-five percent of those who completed the program signed an AD for the first time 27.…”
mentioning
confidence: 99%